SPECIAL CONFISCATION IN THE CASE OF THE OFFENCE OF MONEY LAUNDERING OF PROCEEDS FROM TAX EVASION - Mihai Adrian HOTCA (Challenges of the Knowledge Society)
The academic literature and the case-law are concerned with the relationship between the tax evasion offence and the money laundering offence, when the money laundered come from the first offence. More exactly, the question is whether the penalty of special confiscation of the proceeds from tax evasion may still be imposed on a person who committed both offences and is ordered to pay the tax liabilities. In this article we would like to answer this legal issue, taking into account the relevant legal provisions and caselaw.